Transcriptome Analysis of Apple Leaves with Apple Necrotic Mosaic Virus-Associated Mosaic Symptoms - Dehang Gao; Fei Xing; Qin Yan; Zhixiang Zhang; Binhui Zhan; Meiguang Lu; Yunlong Ma; Hongqing Wang; Shifang Li; Jipeng Xie (Plants)
Apple mosaic disease (AMD) is a widespread viral disease affecting apple-growing regions around the world. Recent studies have identified a novel ilarvirus, apple necrotic mosaic virus (ApNMV), as the major causal agent of AMD in China. However, the molecular mechanisms underlying AMD pathogenesis and the global gene expression changes during mosaic symptom development remain largely unknown. In this study, we performed transcriptome analysis to investigate apple gene responses to AMD. A total of 815 differentially expressed genes (DEGs) were identified in mosaic leaves compared to healthy controls, while 1050 DEGs were found between symptomless leaves (infected with ApNMV) and mosaic leaves. Functional enrichment analysis revealed that these DEGs were predominantly involved in carbohydrate metabolism, oxidation-reduction processes, secondary metabolite biosynthesis, and plant hormone signal transduction. Further biological assays demonstrated that the manifestation of mosaic symptoms in apple leaves was associated with reactive oxygen species (ROS) accumulation and downregulation of ROS-scavenging genes. Collectively, our findings provide new insights into the molecular basis of ApNMV-induced mosaic symptom development in apple and offer potential targets for the management of AMD.